Total ankle arthroplasty with total talus implant printed by 3D printer: . - Soares Baumfel, Daniel; Macedo, Benjamim Dutra; Sanhudo, José Antonio Veiga; Machado, Paula Costa; Magalhães Gomes Macedo, Bruno; Soares Baumfeld, Tiago; Miguel Magalhães Ribeiro, Hugo; Augusto de Souza Nery, Caio (Journal of the Foot & Ankle, 2024)
Describe a case of an aggressive talus tumor treated with total ankle arthroplasty with a patient-specific total talus implant printed on a three-dimensional (3D) printer. A 46-year-old female patient with a history of giant cell tumor treated in the past with partial resection of the talus and replacement with cement, evolving with progressive functional limitation eight years after the initial procedure. In the preoperative, the range of motion was 15° of flexion and 0° of extension, Visual analog scale (VAS) of 8, The American Orthopaedic Foot & Ankle Society (AOFAS) of 45, and the data compiled from the 36-Item Short Form Survey (SF-36) of 50%. The patient was submitted to total ankle arthroplasty with a patient-specific total talus implant printed on a 3D printer. The evaluation six months after the procedure showed a range of motion of 30° of flexion, 8° of extension, VAS of 2, AOFAS of 75, and the data compiled from the SF-36 were 75%. Weightbearing anteroposterior and profile radiographs indicated that the alignment of the implants was maintained. Our study is the first patient- specific total ankle arthroplasty procedure with total talus implant described in the Brazilian literature. Patient-specific total ankle arthroplasty with total talus implantation is a technique that can provide pain relief, maintain movement, and improve patients’ quality of life. Level of evidence IV; Therapeutic study; Case report.